Success factors of academic journals in the digital age - Milan Frederik Klus; Alexander Dilger (Business Research, 2020)
Since the early 1990s, when digitalisation began to open new opportunities for disseminating information, many academic journals started to introduce online services. However, while some studies suggest that online availability and free access to journal articles are positively connected to the number of citations an article receives, little is known about whether being an early adopter of digital services provides journals with a (long-term) competitive advantage in times of digital change. We use data from SSCI-listed management journals to examine which journals pioneered the introduction of digital services, to what extent first-mover advantages can be identified, and which journal characteristics are associated with citation-based performance indicators. Our results show that lower ranked journals were the first to introduce digital services and were beneficiaries of the digital age. Furthermore, we find a negative correlation between general submission fees and journal performance and that the top-performing journals of our sample are those of non-commercial publishers. Our analysis of the relationship between journal performance and the provision of open access contradicts previous studies, as we find no positive correlations between performance and open access on the journal level.
Keywords: I23; L82; L86; M21; O33; 650; Academic journals; Digitalisation; Online availability; Openaccess; Success indicators